The phylogenetic relationships of a new Stream Toad of the genus Ansonia Stoliczka, 1870 (Anura: Bufonidae) from a montane region in Peninsular Malaysia - Davis, Hayden R.; Grismer, L. Lee; Klabacka, Randy L.; Muin, Mohd Abdul; Quah, Evan S.h.; Anuar, Shahrul; Wood, Perry L. Jr.; Sites, Jack W. (Zootaxa, 2016)
Twelve species of Ansonia occur on the Thai-Malay peninsula, of which, five from Peninsular Malaysia, form a monophyletic group. One of these, A. jeetsukumarani, is endemic to the Titiwangsa Mountain Range, in which, we discovered a new population of Ansonia that is not A. jeetsukumarani or even its closest relative. Based on morphology, color pattern, and molecular phylogenetic analyses using the mitochondrial genes 12s and 16s rRNA, we have determined that this new species, A. smeagol sp. nov., forms the sister lineage to an upland, monophyletic group composed of A. jeetsukumarani, A. lumut, A. malayana, and A. penangensis. We have noted similar biogeographic patterns in other taxa from the Titiwangsa Mountain Range in a number of upland lineages in Peninsular Malaysia. We hypothesize that the phylogeographic structure of these upland populations is a result of stochastic processes stemming from interaction of climate-driven forest dynamics and life histories.